If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4v + 6)(2 + v) = 0 Reorder the terms: (6 + 4v)(2 + v) = 0 Multiply (6 + 4v) * (2 + v) (6(2 + v) + 4v * (2 + v)) = 0 ((2 * 6 + v * 6) + 4v * (2 + v)) = 0 ((12 + 6v) + 4v * (2 + v)) = 0 (12 + 6v + (2 * 4v + v * 4v)) = 0 (12 + 6v + (8v + 4v2)) = 0 Combine like terms: 6v + 8v = 14v (12 + 14v + 4v2) = 0 Solving 12 + 14v + 4v2 = 0 Solving for variable 'v'. Factor out the Greatest Common Factor (GCF), '2'. 2(6 + 7v + 2v2) = 0 Factor a trinomial. 2((2 + v)(3 + 2v)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(2 + v)' equal to zero and attempt to solve: Simplifying 2 + v = 0 Solving 2 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + v = 0 + -2 Combine like terms: 2 + -2 = 0 0 + v = 0 + -2 v = 0 + -2 Combine like terms: 0 + -2 = -2 v = -2 Simplifying v = -2Subproblem 2
Set the factor '(3 + 2v)' equal to zero and attempt to solve: Simplifying 3 + 2v = 0 Solving 3 + 2v = 0 Move all terms containing v to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 2v = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 2v = 0 + -3 2v = 0 + -3 Combine like terms: 0 + -3 = -3 2v = -3 Divide each side by '2'. v = -1.5 Simplifying v = -1.5Solution
v = {-2, -1.5}
| 8x+5=14+11x | | -5+(-3) = | | 15x+4y=25 | | 5x^9-40x^7= | | 4(u-5)(-u+2)=0 | | (w+7)(w+2)=0 | | 50+20x=18 | | 25w^6+35w^3=0 | | (x+20.6)*0.604+(65-6.5-0.1*x-2.06)*0.471=150 | | -7(x-2)-3(4-x)=22 | | 2x+186=10x-6 | | 6x^3+3x^2+8x+4= | | 72+x+(x+2)=360 | | 31-4x=5x+15 | | 33-(2c+3)=2(c+5)+c | | x^2+13+6x-4=-3x-9 | | 6-3i/5-6i | | 4k-8/24-12k | | 3+x+(6x+7)= | | x*175=21 | | x*120=18 | | 9x+6=8x-12 | | x^2-3x+8=3x-6 | | -3x+-15=9 | | 6x+7.33=7 | | 140+x+(x-6)=360 | | 28+n=0 | | 2logx-log(2x-10)-1=0 | | 4.5q-2.6-5.7q=-2.2q-3.6 | | y=5x+43 | | 8/9x-2/3=6 | | 2x-39=25 |